Identification and characterization of murine DNAM-1 (CD226) and its poliovirus receptor family ligands - Tahara-Hanaoka, Satoko; Miyamoto, Akitomo; Hara, Ayumi; Honda, Shin-ichiro; Shibuya, Kazuko; Shibuya, Akira (Biochemical and biophysical research communications, 2005)
The leukocyte adhesion molecule DNAM-1 (CD226) is a member of the immunoglobulin superfamily and constitutively expressed on the majority of CD4+ and CD8+ T lymphocytes, natural killer (NK) cells, monocytes/macrophages, and a subset of B lymphocytes. The poliovirus receptor (PVR; CD155) and its family member nectin 2 (CD112) have recently been identified as the ligands for DNAM-1. Interaction of DNAM-1 with the ligands induces NK cell- and CD8+ T cell-mediated cytotoxicity and cytokine secretion. However, in vivo function of the receptor–ligand interaction has remained unclear. Here, we identified murine DNAM-1 and PVR homologues that physically and functionally bind each other. We demonstrated that ligand binding of murine DNAM-1 induced a costimulatory signal in antigen-specific CD8+ T cells. These results should provide a useful animal model to explore a role of DNAM-1 in immune responses in vivo.